Development and validation of a postgraduate anaesthesiology core curriculum based on Entrustable Professional Activities: a Delphi study - Moll-Khosrawi, Parisa (GMS Journal for Medical Education, 2020)
Background: Postgraduate training curricula should not be based on time-spans or predefined numbers of performed procedures. One approach to link competencies to clinical tasks is the concept of Entrustable Professional Activities (EPA). The goal of this study was the definition, ranking and validation of EPAs for anaesthesiology postgraduate training and the creation of an anaesthesiologic core curriculum. Methods: Anaesthesiologists of different levels of training participated in the study (single-center, cross-sectional) . First, an expert group defined a preliminary list of EPAs. Then a first Delphi round (n= 47 participants) was applied to identify daily anaesthesiology tasks with the goal to define EPAs. From the first Delphi round a new set of EPAs was defined, using the template and mapping method. Through an alignment process, conducted by the expert group, the preliminary EPAs and the new set of EPAs from the first Delphi round were summarised into a new list of EPAs. This list was presented to the study participants in a second Delphi round (n=80 participants), with the goal to validate and rank each EPA and to define the year of entrustment. For this purpose, participants were asked in the second Delphi round if each EPA should be included into an anaesthesiology core curriculum and in which year of training entrustment should take place. Furthermore, they were asked to rank each EPA on a numeric scale, defining its importance. From this numeric scale, the content validity index (CVI) for each EPA was calculated.Consensus of the results from the second Delphi round was calculated, using the one-way random effects model to calculate Intra-Class-Correlations (ICC). Percentages of agreement among the whole set of EPAs of this study and a previously published set of EPAs were computed.Results: A core-curriculum comprising of 39 EPAs was developed. The EPAs were subdivided into superior/high and inferior/low scoring EPAs, reflecting their importance and were mapped to the year of entrustment. The results reached high consensus among the different participating anaesthesiologist groups (overall agreement was 0.96 for the CVI of each EPA and 0.83 for the year in which the EPAs should be entrusted). Agreement with the previously defined set of EPAs was 73.3%.Conclusion: This study provides a further step in transforming postgraduate anaesthesiology training into a more contemporary approach. Other studies are necessary to complete and amend the presented core curriculum of EPA based postgraduate anaesthesiology training.